(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Background: The racial variation in genetic susceptibility of Type2 diabetes mellitus is well established. The stages of impaired fasting glucose (IFG) and/or Impaired glucose tolerance (IGT) (collectively known as ‘prediabetic stages) are combined to be intermediate in the natural history of diabetes, but their genetic susceptibility are still a matter of investigation. Family study is the primary step to explore genetic susceptibility. In particular, there has been no study in Bangladesh related to genetics of prediabetes. Objectives: The present study aimed to explore the genetic susceptibility of prediabetes in Bangladeshi population by observing the clustering of dysglycemia in first degree relatives of prediabetes. Methodology: The study was designed as an experimental group comparison study. Newly detected prediabetic subjects (isolated IFG, IGT, IFG+IGT) were collected from BIRDEM OPD and reconfirmed by OGTT following WHO guidelines and sub grouped. Relatives of the prediabetes, up to first generation, were included as cases and termed as R-IFG (first degree relatives of IFG), R-IGT (first degree relatives of IGT), R-IFG-IGT (first degree relatives of IFG-IGT) corresponding to the subgroups of prediabetes. Each relative underwent an OGTT following the same guideline. Blood glucose was measured by glucose oxidase method. Results: Different types of prediabetic subjects (IFG, IGT, IFG+IGT) and their first degree relatives (R_IFG, R_IGT, R_IFG+IGT) were studied. Among 41 first degree relatives of IFG (R_IFG), 2 (4.9%) had IFG, 4 (9.8%) had IGT, 1 (2.4%) had combined IFG+IGT, 5 (12.5%) had T2 DM and 29 (70.7%) had normoglycemia. Among 116 first degree relatives of IGT (R_IGT) none (0.00%) had IFG, 15 (12.9%) had IGT, 2 (1.7%) had combined IFG+IGT, 22 (19%) had diabetes and 77 (66.4%) having absolutely normal OGTT reports. Among 76 first degree relatives of IFG+IGT (R_IFG+IGT), 2 (2.6%) had IFG, 4 (5.3%) had IGT, 1 (1.3%) had combined IFG+IGT, 19 (25%) had diabetes and 50 (65.8%) were normoglycemic. Conclusion: Clustering of pre-diabetes and diabetes is present in families of prediabetic subjects and they should be taken as a major target for primary prevention of these disorders. Key words: Prediabetes; IFG; IGT; IFG+IGT; First degree relatives; Glucose intolerance. DOI: 10.3329/jbsp.v29i1.7167 J Bangladesh Coll Phys Surg 2011; 29:21-26